Evaluation of body measurements of Limousin heifers by backward regression analysis in Western Hungary - Tőzsér, János; Vertséné Zándoki, Rita; Kosztolányiné Szentléleki, Andrea; Tarr, Bence; Szűcs, Márton (Animal welfare, Ethology and Housing Systems (AWETH), 2023)
Body measurements of yearling Limousin heifers (height at withers, HW, cm; tail height, HT, cm; back length, LB, cm; width at shoulders, WS, cm; hip bone width, WHB, cm; pin width, WP, cm) were taken in 7 nucleus farms in the Western Hungarian region n=322). The aim was to collect information on body sizes of yearling heifers and to work out regression equations for body measurements and live weight. Backward regression analyses and multifactorial regression analysis were completed using software SPSS 24.0. Results of backward analysis revealed different R2% values were obtained (49.2, 92.5) for prediction of withers’ height, tail height, length of back, and width of shoulders. Determination coefficients above 90% in cases of withers height and tail height imply that these parameters can be predicted by regression models accurately so one of them can be estimated. Both traits are useful in breeding strategy for planning corrective matings. For length of back and width at shoulders, precise prediction was not possible by these parameters. More researches are needed to find out better fitting models. Live weight could not be estimated accurately enough (R2=68.5 – 68.6%) from the available body measurements (withers height, tail height, length of back, width at shoulders, width at hip bones). Since other results imply that chest girth is strongly correlated with live weight, it is considerable for Hungarian Limousine breeders to involve this trait into measured parameters.
Keywords: body measurements; Limousin breed; heifers; backward regression analysis